Gut microbiota and viral respiratory infections: microbial alterations, immune modulation, and impact on disease severity: a narrative review - El-Khoury, Gaelle; Hajjar, Crystel; Geitani, Regina; Karam Sarkis, Dolla; Butel, Marie-José; Barbut, Frédéric; Abifadel, Marianne; Kapel, Nathalie (Frontiers in Microbiology, 2025)
Respiratory viral infections are a major public health concern, accounting for millions of infections annually and contributing significantly to global morbidity and mortality. Influenza and respiratory syncytial virus (RSV) have long been recognized as critical pathogens, while the recent emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the COVID-19 pandemic. These viruses typically affect both the upper and lower respiratory tracts and can cause a broad spectrum of clinical manifestations, ranging from mild symptoms to severe respiratory failure and multi-organ dysfunction. Gastrointestinal symptoms are also frequently reported, suggesting a potential link between respiratory viruses and gut microbiota alterations. This connection highlights the role of the gut microbiota in disease pathophysiology. This narrative review summarizes current evidence on gut microbiota changes associated with SARS-CoV-2, influenza, and RSV infections. It further explores the microbiota’s role in immune regulation and host homeostasis, and discusses the potential of microbiota-targeted strategies in the prevention and management of acute respiratory syndromes.